2022
DOI: 10.1088/2053-1591/ac48b8
|View full text |Cite
|
Sign up to set email alerts
|

A review of the function of using carbon nanomaterials in membrane filtration for contaminant removal from wastewater

Abstract: Water is a necessity for all living and non-living organisms on this planet. It is understood that clean water sources are decreasing by the day, and the rapid rise of Industries and technology has led to an increase in the release of toxic effluents that are discharged into the environment. Wastewater released from Industries, agricultural waste, and municipalities must be treated before releasing into the environment as they contain harmful pollutants such as organic dyes, pharmaceuticals wastes, inorganic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 45 publications
0
22
0
1
Order By: Relevance
“…It was evident that it may easily create composites with various metals (N 2 , O 2 , Si, etc), compounds (Al 2 O 3 , Fe 3 O 4 , etc), carbonaceous materials (biochar, carbon nanotubes, graphene, graphene oxide, activated carbon, etc), and agrowaste (coconut husk, tea, etc). Chitosan's thermal and mechanical stability can be increased by utilizing grafting and cross-linking agents and various biopolymers such as cellulose [147,[154][155][156][157][158][159]. Chitosan derived from chitin can be modified using a variety of synthesis techniques (electrospraying, electrospinning, ionotropic gelation, reverse micelle, and spray drying), allowing it to be used in a variety of fields, including agriculture, biomedical, agro-waste management, water treatment, microbial fuel cells, cosmetics, textiles, paper, and pulp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was evident that it may easily create composites with various metals (N 2 , O 2 , Si, etc), compounds (Al 2 O 3 , Fe 3 O 4 , etc), carbonaceous materials (biochar, carbon nanotubes, graphene, graphene oxide, activated carbon, etc), and agrowaste (coconut husk, tea, etc). Chitosan's thermal and mechanical stability can be increased by utilizing grafting and cross-linking agents and various biopolymers such as cellulose [147,[154][155][156][157][158][159]. Chitosan derived from chitin can be modified using a variety of synthesis techniques (electrospraying, electrospinning, ionotropic gelation, reverse micelle, and spray drying), allowing it to be used in a variety of fields, including agriculture, biomedical, agro-waste management, water treatment, microbial fuel cells, cosmetics, textiles, paper, and pulp.…”
Section: Discussionmentioning
confidence: 99%
“…When the chitin deacetylation levels come to nearly half (contingent upon the beginning of the polymer), it becomes dissolvable in low pH solvents termed chitosan. Chitosan and its subordinates have pragmatic applications as arrangements, suspensions, particles, for example, dabs, tars, circles, nanoparticles, and wipes, gels and hydrogels, froths, layers and movies, strands, infinitesimal strings, and frameworks in many areas: medication and medicine, drug stores, cosmetology, cleanliness, and individual consideration, food and nourishment, agribusiness and agrochemistry, material and paper ventures, palatable entertainment world and bundling, biotechnology, science, and drink fields, ecology, photography, and such arising areas as nutraceuticals, practical materials and cosmetic-materials, cosmeceuticals, nanotechnology, and hydroponics [148][149][150][151][152][153][154][155].…”
Section: Miscellaneous Applicationsmentioning
confidence: 99%
“…Then, to look into CNC fermentation in human digestion, CNC may interact with the gut microbiota and impact its metabolism in the distal ileum and colon. Researchers must continue to work on their technological and nutritional characteristic evaluation, safety testing, and, most significantly, the topic of food application regulation [167,[169][170][171][172][173].…”
Section: Future Developments and Possibilitiesmentioning
confidence: 99%
“…While metals and some alloys were the only feed materials used in the primitive stages of DED, a broad spectrum of materials are currently being used in the additive manufacturing industry [13]. Unconventional materials such as superalloys, polymers, nanomaterials, biomaterials, or even bio-waste materials have proven to be suitable replacements for conventional metals and alloys [18][19][20][21][22][23][24][25]. Even though not ready to be used at an industrial scale, recent research on these new materials has shown promising results about using them for mass production in the future.…”
Section: Types Of Feed Materials Used In Dedmentioning
confidence: 99%